Security Considerations for E-Mental Health Interventions - Bennett, Kylie; Bennett, Anthony James; Griffiths, Kathleen Margaret (JMIR Publications, 2010)
Security considerations are an often overlooked and underfunded aspect of the development, delivery, and evaluation of e-mental health interventions although they are crucial to the overall success of any eHealth project. The credibility and reliability of eHealth scientific research and the service delivery of eHealth interventions rely on a high standard of data security. This paper describes some of the key methodological, technical, and procedural issues that need to be considered to ensure that eHealth research and intervention delivery meet adequate security standards. The paper concludes by summarizing broad strategies for addressing the major security risks associated with eHealth interventions. These include involving information technology (IT) developers in all stages of the intervention process including its development, evaluation, and ongoing delivery; establishing a wide-ranging discourse about relevant security issues; and familiarizing researchers and providers with the security measures that must be instituted in order to protect the integrity of eHealth interventions.